The Efficacy of Behavior Management for Depression in Dementia Patients: A Systematic Review and Meta-Analysis - K. Thu, Win; Lwin, Nay; Yasky, Jaime; Bambling, Matthew; K.K. Aye, San (Journal of Aging Research And Healthcare, 2018)
Overview: Dementia is a serious brain disease that impacts negatively in several areas of patient’s functioning. Depression has a strong link with dementia and is part of the behavior and psychological symptoms (BPSD). Behavior management for depression is recommended as a first-line psychological treatment for dementia patients. However, there are no systematic reviews examining the efficacy of behavior management for depression in dementia. Objective: To examine the efficacy of behavior management (BM) for depression in dementia patients. Methods: Five electronic databases were searched (1999 to 2015) for randomized controlled trials (RCTs) which were selected according to eligibility criteria. Data was pooled, quality assessment was completed, and a meta-analysis was performed. Results: This review included ten randomized controlled trials. In the four studies where behavior management was a focused intervention, no significant treatment effect was observed (standardized mean difference SMD -0.20; 95 % CI -0.96 to 0.56). In the remaining six studies in which behavior treatment was involved as a component, the analysis showed a trend favored the intervention, but it was not significant (SMD -0.12; 95 % CI -0.25 to 0.01). Conclusion: There is no evidence for behavior management alleviating depression in dementia patients. Future research examining the efficacy of specific behavior management techniques for milder forms of dementia and multimodal interventions are recommended.
Keywords: behavior management; depression; dementia